Pneumatic power plant as an alternative source of ecologically clean domestic energy - Квашнин, Валерий Олегович; Квашнин, Владислав Валериевич (Eastern-European Journal of Enterprise Technologies, 2014)
The solution of the problem of unstable parameters of the output voltage of wind power plants because of the inconstancy of wind flow, limiting the scope of their application based on the transition to the development of pneumatic power plant, containing energy accumulators in the form of high-pressure compressed air tanks in its structure is considered in the paper. Concrete design of low-capacity pneumatic power plant is proposed. The issue of calculating and selecting the sizes of energy accumulators in the form of high-pressure tanks, taking into account certain intervals of the wind flow is studied. Duration of continuous operation of the electrical load with power of up to 1 kW at various energy accumulator capacities is determined. The choice of power of the load consumed from the condition of its uninterruptible power supply with the presence of constraints on the sizes of the energy accumulators, their charging rate, installed capacity of the power generator, type size of the wind wheel, as well as constancy of the wind flow strength and speed are shown.